Nyonya food, culinary capital and women’s empowerment in Stella Kon’s Emily of Emerald Hill and Selina Siak’s The Woman who Breathed Two Worlds - Siti Zaharah Syahiera Fauzi,; Siti Nuraishah Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Nyonya food is part of the construction of Peranakan Chinese group identity generally, but is also central to notions of Peranakan Chinese femininity, which emphasizes, among others, their mastery of culinary skills. The association of Nyonya food with Peranakan Chinese women may signal the secondary roles that are assigned to them by a patriarchal community, as foodwork is often considered supplementary in nature. However, in this paper, we propose a different way of reading Peranakan Chinese women’s relationship with food, as one that empowers them as heads of their households, decision-makers and custodians and transmitters of their community’s culture and identity. This paper sets out to explore how Nyonya food empowers Peranakan Chinese women in two literary texts: Stella Kon’s play Emily of Emerald Hill (1989) and Selina Siak’s historical novel, The Woman who Breathed Two Worlds (2016) by applying the concept of culinary capital to their depictions of women, food and foodwork. Through this analysis, we will demonstrate that food and foodwork do not merely reinforce Peranakan Chinese women’s gendered roles or reduce them to consumable products in literary texts, but rather endow them with culinary capital with which they can exercise their power and influence within their families and their communities. The protagonists of the works selected are formidable Nyonyas who engage in acts of challenging the patriarchal nature of their respective environments, and food is significant in their assertions of their power.